THE MEDIA ROLE ON CHEMISTRY SCIENCE INSTRUCTION IN COLLEGE - Muhammad Noer, Asmadi (Proceeding 7th International Seminar on Regional Education, 2015)
AbstractMedia is a kind of tool to deliver material contents to learners (students). Chemistry contains much abtract concepts elusively, such as the concept of the atom, electronic structure in the atomic structure, ionization energy, ionic activities, reaction and reaction speed and etc. All of the concepts is not enough just described verbally, orally to students but it is needed to explained visually through media, in order to have a comprenhensif knowledge. Right now, it is well-known a multimedia such as Macromedia tools that the difficult contents can be more easilly understood. through pictures and animations available made it. It will be conducted a meaningful learning instruction through chemistry lesson in science education college. Macromedia such as flash-media program, Prezi,etc. It is easly able to explain concepts to the learners. Chemistry learning research results shows that some difficult topics make it students more interested in in learning and improved their competenciesn also.Keywords: media role, content abtract, chemistry education.